Phenolic content and antioxidant activity of defatted rice bran as affected by simulated gastrointestinal PH - Chan, Kim Wei; Ismail, M. (2011)
Rice bran is a low cost by-product from the rice-milling industry. The objective of the present study was to investigate the phenolic and antioxidant activity changes of defatted rice bran under simulated gastrointestinal pH.Slurry of defatted rice bran and 3 other commercial flours (defatted wheat, sweet potato and rice flours) were respectively subjected to simulated gastrointestinal pH adjustment. Supernatants of the tested samples were obtained through centrifugation and its total pehnolic content (by Folin-Ciocalteu reagent) as well as antioxidant activity were evaluated. Results from the analyses shows that adjustment of gastrointestinal pH improved total phenolic content and antioxidant activities (DPPH scavenging activity, ABTS free radical scavenging activity and beta-carotene bleaching activity assay) of all tested samples (P<0.05). Besides, defatted rice bran exhibited higher antioxidant activity and phenolic content than all tested commercial flours (P<0.05). In conclusion, defatted rice bran is a very potential raw ingredient for development of nutraceutical and functional food products due to its high phenolic content and antioxidant activity as compared to other commercial edible flours. Besides, gastrointestinal pH adjustment also gives a clearer picture on the actual antioxidant activity of defatted rice bran in in-vivo digestive tract.